Students’ Perceptions of the Benefits of Multimodal Texts Used by English Teachers at SMA Uswatun Hasanah Padang Panjang - Syarifah Hayatul Fitri; Putra, Hendra Eka; Suyono, Suyono; Elfi, Elfi; Afriandi, Muhamad Argi (Universitas Ahmad Dahlan, 2025)
In the rapidly evolving digital era, multimodal texts—integrating visual, auditory, and textual elements—have become increasingly essential in English language instruction. However, limited research exists on how students perceive the pedagogical value of these texts in secondary education, especially within the Indonesian context. This study aims to explore students’ perceptions of the benefits of multimodal texts as used by English teachers at SMA Uswatun Hasanah Padang Panjang during the 2024/2025 academic year. Employing a quantitative approach with a descriptive design, data were collected from 28 eleventh-grade students selected through total sampling. A closed-ended questionnaire using a five-point Likert scale was administered, and data were analyzed based on Djemari’s perception classification (as cited in Fitri, 2016). Findings revealed that the majority of students held favorable views: 46.4% had a positive perception, 42.9% had a strongly positive perception, and only 10.7% had a negative perception. Notably, students perceived multimodal texts positively in the cognitive and conative components and strongly positive in the affective domain. These results highlight the importance of integrating multimodal strategies to enhance student engagement and comprehension in English learning. The study contributes to current ELT practices by underscoring the pedagogical relevance of multimodal texts in fostering meaningful and emotionally engaging learning experiences.